International Standardization and Trade Regulation Exploring Linkages Between International Standardization Organizations and International Trade Agreements - Klotz, Sebastian (BRILL, 2024)
International standards play an important role in the regulation of global trade. This book investigates who actually develops these standards and how the design of international trade agreements influences international standardization, and vice versa
Description based on publisher supplied metadata and other sources